2007
DOI: 10.1182/blood-2007-03-078303
|View full text |Cite
|
Sign up to set email alerts
|

High levels of the BCR/ABL oncoprotein are required for the MAPK-hnRNP-E2–dependent suppression of C/EBPα-driven myeloid differentiation

Abstract: The inability of myeloid chronic myelogenous leukemia blast crisis (CML-BC) progenitors to undergo neutrophil differentiation depends on suppression of C/EBPα expression through the translation inhibitory activity of the RNA-binding protein hnRNP-E2. Here we show that “oncogene dosage” is a determinant factor for suppression of differentiation in CML-BC. In fact, high levels of p210-BCR/ABL are required for enhanced hnRNP-E2 expression, which depends on phosphorylation of hnRNP-E2 serines 173, 189, and 272 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 65 publications
4
90
0
1
Order By: Relevance
“…This hypothesis is further supported by the ability of BCR-ABL to block myeloid differentiation. 5,6 Overall, these data suggest that the 'oncogene dosage' is a determinant factor for the differentiation block in BC-CML and that the progression to BC could be linked to an abnormal control of BCR-ABL expression during myeloid differentiation with ensuing maturation block. Unfortunately, the mechanisms leading to the deregulated expression of BCR-ABL in BC are not known.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis is further supported by the ability of BCR-ABL to block myeloid differentiation. 5,6 Overall, these data suggest that the 'oncogene dosage' is a determinant factor for the differentiation block in BC-CML and that the progression to BC could be linked to an abnormal control of BCR-ABL expression during myeloid differentiation with ensuing maturation block. Unfortunately, the mechanisms leading to the deregulated expression of BCR-ABL in BC are not known.…”
Section: Introductionmentioning
confidence: 97%
“…Previous works showed that the BCR-ABL expression level is critical for this differentiation block. 5 CEBPa represents the principal inducer of granulocytic differentiation; in BC-CML primary cells, CEBPa protein is almost undetectable, although its mRNA is expressed at high levels. 6 Perrotti et al 6 showed that BCR-ABL upregulates the expression of hnRNPE2, an RNA-binding protein that, by its interaction with CEBPa mRNA, inhibits CEBPa translation and causes its suppression at the protein level: thus hnRNPE2 and CEBPa protein expression levels inversely correlate.…”
Section: Introductionmentioning
confidence: 99%
“…6.15 (32D-BCR/ABL) cells have been previously described. 26 Ficoll-separated bone marrow cells from patients with AML were used freshly or after freezing in liquid nitrogen and cultured in IMDM (Gibco) with 20% FBS, 1% P/S, and 1% glutamine. CDDO was synthesized by Dr Sporn, Dartmouth, NH, and was diluted in dimethyl sulfoxide (DMSO) to obtain working concentrations, and identical volumes of DMSO and CDDO (in DMSO) were added to the cultures.…”
Section: Cells Transfection and Reagentsmentioning
confidence: 99%
“…24,25 In these AML subtypes, re-expression of functional CEBPA restores granulocytic differentiation, suggesting that suppression of CEBPA is essential for the phenotype of AML blasts. Likewise, differentiation of myeloid progenitors in chronic myelogenous leukemia (CML) blast crisis is disturbed by BCR/ABL-induced suppression of CEBPA mRNA translation through the activation of the MAPKhnRNP E2 pathway 23,26 . Here, we provide evidence that CDDO potently induces granulocytic differentiation of leukemic cell lines and patient-derived primary AML blasts by translationally enhancing the expression and function of CEBPA through a mechanism that involves increase of p42 and the p42/p30 ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation